If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + -1 = 15x + -100 Reorder the terms: -1 + 16x = 15x + -100 Reorder the terms: -1 + 16x = -100 + 15x Solving -1 + 16x = -100 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -1 + 16x + -15x = -100 + 15x + -15x Combine like terms: 16x + -15x = 1x -1 + 1x = -100 + 15x + -15x Combine like terms: 15x + -15x = 0 -1 + 1x = -100 + 0 -1 + 1x = -100 Add '1' to each side of the equation. -1 + 1 + 1x = -100 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = -100 + 1 1x = -100 + 1 Combine like terms: -100 + 1 = -99 1x = -99 Divide each side by '1'. x = -99 Simplifying x = -99
| 10=4+2y | | x=34-8/7 | | 2+-7-5t=11 | | (x^2-6x+2)+(-3x^2+5x+7)= | | 3x+6+4x=34 | | 7.34=.3x-x | | 35+-2y+x+2y=125 | | y-1/3=2/3 | | 8x+2y+26=3y | | x-7.34=.3x | | (5/6)t+4=2-(1/6)t | | ifz^4=16factorisez^4-16 | | 3x+5=-2-10 | | 2m-5n=200 | | 4x=-51 | | -5=x-1 | | x/3=4+x | | 10(5p-1)=7(7p-3) | | 90+x+2y=125 | | -(a-9)=3(a+5)+2 | | 3(7+3n)=6(6+n) | | 4x+36=21x-15 | | (2)(0)-2= | | 18x-45=-12 | | 4x+36=21-15 | | 16=0.25s-4 | | 3d+6(d-7)=30 | | -n-8=-4n+10 | | 6+bx=b-4 | | 4y+10+90=180 | | -6=r+8-3r | | 0.25(87-4)=z+8-2z |